Decentralized autonomous organizations (DAOs): Stewardship talks but agency walks - Alawadi, Asma; Kakabadse, Nada; Kakabadse, Andrew; Zuckerbraun, Sam (Journal of business research, 2024)
Although the governance of Decentralized Autonomous Organizations (DAOs) has attracted the interest of several academics, few studies have empirically examined how DAOs are governed. We use an exploratory, inductive approach to comprehensively examine how DAOs are currently governed and the ramifications of this. We conducted in-depth interviews with 20 DAO members from a variety of sectors to identify how they arrange their voting processes, distribute collaborative decision-making, and maintain their tokens. Three themes emerge from the thematic analysis of the data: (1) voting structure, (2) proposal management, and (3) token management. Participants describe the notion of DAOs as closely aligned with stewardship philosophy, encompassing collaborative and altruistic activity toward a common purpose. However, the operations and methods implemented are more oriented toward agency viewpoints due to their reliance on incentive-based processing and are based on a lack of trust among DAO stakeholders. This study provides empirical insights into DAO governance mechanisms.11Decentralized autonomous organizations (DAOs).